2018
DOI: 10.1002/bdr2.1419
|View full text |Cite
|
Sign up to set email alerts
|

Uterine natural killer cells: To protect and to nurture

Abstract: During the course of pregnancy, the maternal-fetal interface is tightly regulated and undergoes dynamic changes that promote the successful development of the semi-allogeneic fetus. In response to embryo implantation, the uterus remodels with maternal immune cells occupying the maternal-fetal interface and uterine natural killer (uNK) cells becoming the most prominent leukocyte. Recently, uNK cells have been discovered to be heterogeneous, including conventional NK (cNK) and tissue-resident NK (trNK) cells. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
(79 reference statements)
2
22
0
Order By: Relevance
“…We recently used the parabiosis model together with experimentallyinduced decidualization to study early pregnancy events and demonstrated that trNK cells do not circulate. Rather, trNK cells proliferate locally and expand the uNK cell pool with minimal cNK cells contributions (13,27). These data support a two-wave hypothesis for uNK cell accumulation during typical pregnancies (13,27,51).…”
Section: Origin Of Unk Cellssupporting
confidence: 68%
See 2 more Smart Citations
“…We recently used the parabiosis model together with experimentallyinduced decidualization to study early pregnancy events and demonstrated that trNK cells do not circulate. Rather, trNK cells proliferate locally and expand the uNK cell pool with minimal cNK cells contributions (13,27). These data support a two-wave hypothesis for uNK cell accumulation during typical pregnancies (13,27,51).…”
Section: Origin Of Unk Cellssupporting
confidence: 68%
“…Rather, trNK cells proliferate locally and expand the uNK cell pool with minimal cNK cells contributions (13,27). These data support a two-wave hypothesis for uNK cell accumulation during typical pregnancies (13,27,51). The first wave involves local proliferation of trNK cells during decidualization; the second wave postulates the accumulation of cNK cells recruited into the decidua basalis during placentation.…”
Section: Origin Of Unk Cellssupporting
confidence: 64%
See 1 more Smart Citation
“…Potentially, the most relevant immune cells during pregnancy are NK cells. In mice, during the non-menstrual period, NK cells make up 30% of endometrial lymphocytes, and this number increases significantly (70% of lymphocytes) during pregnancy and decidualization [ 188 , 189 ]. Almost all the NK cells in the non-pregnant uterus (endometrium) and pregnant uterus (decidua) are CD56 bright [ 31 , 190 ].…”
Section: Uterine Nk Cellsmentioning
confidence: 99%
“…These cells are not vestigial and have been sustained through evolution for a variety of reasons [2]. They are postulated to serve relevant roles in reproductive success, surveillance of cancerous cells and control of viral infections [3][4][5][6]. This is supported by strong evidence accumulated in a wide variety of animal models and in select human contexts collected over the nearly 45 years since NK cells were named as such.…”
Section: Nkd-directed Primer On Nk Cell Biology and Functionmentioning
confidence: 97%